The Immune Syntax Revisited: Opening New Windows on Language Evolution - Benítez-Burraco, Antonio; Uriagereka, Juan (Frontiers in Molecular Neuroscience, 2016)
Recent research has added new dimensions to our understanding of classical evolution, according to which evolutionary novelties result from gene mutations inherited from parents to offspring. Language is surely one such novelty. Together with specific changes in our genome and epigenome, we suggest that two other (related) mechanisms may have contributed to the brain rewiring underlying human cognitive evolution and, specifically, the changes in brain connectivity that prompted the emergence of our species-specific linguistic abilities: the horizontal transfer of genetic material by viral and non-viral vectors and the brain/immune system crosstalk (more generally, the dialogue between the microbiota, the immune system, and the brain).